Struktur Anatomi Daun Mangrove Jenis Avicennia lanata Ridl. dan Sonneratia Alba J.E. Smith di Desa Siney Tengah, Parigi Moutong - Antika, Rindi; Isnainar, Isnainar; Febriawan, Aan; Nurdin, Musdalifah; Mawaddah, Hayyatun; Lilies, Lilies (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe and compare the anatomical structure of mangrove leaves of Avicennia lanata Ridl. and Sonneratia alba J.E. Smith in the coastal area of Central Siney Village, South Tinombo District, Parigi Moutong Regency. This study used a quantitative descriptive approach and was conducted at the Biology Education Laboratory, Faculty of Teacher Training and Education, Tadulako University in November 2024. The research samples were A. lanata and S. alba mangrove leaves collected from the research location, with data obtained through microscopic observation, documentation, and questionnaires. The results showed that there were differences in the anatomical structure of the leaves of the two mangrove species, especially in the type of stomata, the thickness of mesophyll tissue, and the development of salt glands. Avicennia lanata has actinocytic stomata and more developed salt glands, while Sonneratia alba has cyclic stomata and thicker pole tissue. Both have similar basic leaf structures, such as cuticle, epidermis, cortex, and xylem and phloem transport tissues. Thus, there are distinctive anatomical adaptations in each species, reflecting survival strategies in the mangrove ecosystem.